'Would you eat cultured meat?': Consumers' reactions and attitude formation in Belgium, Portugal and the United Kingdom. (April 2015) - Verbeke, Wim; Marcu, Afrodita; Rutsaert, Pieter; Gaspar, Rui; Seibt, Beate; Fletcher, Dave; Barnett, Julie
Abstract: Cultured meat has evolved from an idea and concept into a reality with the August 2013 cultured hamburger tasting in London. Still, how consumers conceive cultured meat is largely an open question. This study addresses consumers' reactions and attitude formation towards cultured meat through analyzing focus group discussions and online deliberations with 179 meat consumers from Belgium, Portugal and the United Kingdom. Initial reactions when learning about cultured meat were underpinned by feelings of disgust and considerations of unnaturalness. Consumers saw few direct personal benefits but they were more open to perceiving global societal benefits relating to the environment and global food security. Both personal and societal risks were framed in terms of uncertainties about safety and health, and possible adverse societal consequences dealing with loss of farming and eating traditions and rural livelihoods. Further reflection pertained to skepticism about 'the inevitable' scientific progress, concern about risk governance and control, and need for regulation and proper labeling. Highlights: Views on cultured meat were elicited through focus groups and online deliberation. Initial reactions were underpinned by feelings of disgust and perceived unnaturalness. Few personal, but potential societal benefits were acknowledged. Both personal risks and potential adverse societal consequences were envisaged. Deeper concerns relate to controllability, regulation and labeling.